Sazonalidade atmosférica e suas relações com as formigas (hymenoptera, formicidae) na Flona de Caxiuanã-PA - SANTOS, Sergio Rodrigo Quadros dos (2019)
The temporal variability of ant fauna collected in Caxiuanã-PA during the protocol-litter ants Project TEAM / Caxiuanã were studied from the local meteorological conditions observed during the months of January and April (rainy season) and July and October (less rainy season) for the period 2006 to 2007. For this, we used meteorological data from micrometeorological tower Caxiuanã. During the rainy season, it was noted the predominance of high values of precipitation, soil moisture and low air temperatures. At least rainy season, we observed the opposite behavior of the rainy season for the meteorological variables. In general, we found that the frequency of ants is greater when there is decrease in rainfall, soil moisture, and increased air temperature. There was also that the statistical correlation (second order polynomial) between the atmospheric variables and the frequency of ants clearly show that they occur in reverse order for the precipitation and soil moisture, and direct to the air temperature. These results suggest that most formicidae thrive in hot and humid environments